"Nostalgic Elegance": The Enduring Style of the Gibson Girl. (2nd January 2021) - Simon, Joshua; Mamp, Michael
Abstract : This paper offers new perspectives on the sartorial style of the Gibson Girl archetype, the ideal of feminine beauty at the turn of the twentieth century, and its reinterpretation and prevalence post-World War II. We explore this nostalgic resurgence of turn-of-the-century style, identify which characteristics defined it, and examine its dissemination across the fashion industry. From the couture designs of Dior and Schiaparelli to sew-at-home patterns like those offered by Butterick, Simplicity, and McCall, the resurgence of the Gibson Girl's sartorial style influenced fashion and gained further popularity through presentations in film, theater, and retail merchandising.